ANALISIS PENERAPAN PEMBELAJARAN BERBASIS HOTS PADA PROGRAM KEAHLIAN OTOMATISASI TATA KELOLA PERKANTORAN SMK NEGERI DI KOTA SURAKARTA - Andreas Bagas Kiswara (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
The objective of the research was to find out: (1) the implementation of HOTS- basedlearning; (2) constraints with the implementation of HOTS-based learning; and (3) solutions taken to deal with the constraints with the implementation of HOTS- based learning. This study was qualitative research with a case study approach. Data source derived from 12 informants coming from SMK Negeri 1 Surakarta, SMK Negeri 3 Surakarta, and SMK Negeri 6 Surakarta,  i n c l u d i n g  t h e Deputy  of Headmaster for Curriculum Division, Chairperson, teachers program, and students of Office Management Automation Specialties program. The techniques  of collecting data used were interview, observation, and document analysis. Data validation was carried out using source and method triangulation. Data analysis was carried out using descriptive analytical techniques. The research procedure consisted of pre-field, field, data analysis, and report writing stages. The results of the research were as follows. (1) The implementation of learning in three Vocational High Schools studied applied HOTS-based learning after the use of 2013 curriculum. In the learning preparation stage, the learning implementation plan has been organized entirely and systematically based on the textbook and is oriented toward high-order thinking skills. (2) Constraints found in the implementation of HOTS-based learning were: teachers’ understanding of and preparedness for HOTS-based learning, learning plan and evaluation, and inadequate  learning  infrastructure.  (3)   Solutions   taken   to   deal   with   the constraints included holding socialization and workshop activities related to HOTS- based learning, using varying learning models, and motivating the students.